Literatur Riview terhadap Turnover Intention: Pengaruh Kepuasan Kerja dan Stres Kerja - nanda hanifah putri (Penerbit Goodwood, 2023)
Purpose: This study aims to determine the effect of Job Satisfaction and Job Stress on Employee Turnover Intention. Research Methodology: This study uses